2010
DOI: 10.1080/09712119.2010.9707162
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Effects ofRosa damasceneMill in Dogs

Abstract: Abbaszadeh, M., Kazerani, H.R. and Kamrani, A. 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…R. damascena is a dosedependent laxative in dogs, thus causing diarrhea at 90 mg/kg low doses. During the intervention, there are no side effects, its laxative effect has been successfully performed, and it can also have a therapeutic value (21). No significant adverse events were observed in our study during the use of R. damascena products except for mild nausea, mild flatulence, and mild diarrhea in limited cases that did not disturb patient ingestion.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…R. damascena is a dosedependent laxative in dogs, thus causing diarrhea at 90 mg/kg low doses. During the intervention, there are no side effects, its laxative effect has been successfully performed, and it can also have a therapeutic value (21). No significant adverse events were observed in our study during the use of R. damascena products except for mild nausea, mild flatulence, and mild diarrhea in limited cases that did not disturb patient ingestion.…”
Section: Discussionmentioning
confidence: 62%
“…The laxative and stimulating effect of R. damascena on the intestines in recent in vivo studies (19)(20)(21), the omission of the side effects in routine consumption (3), convenient access and maintenance of this herb, and popular acceptance are important reasons behind the selection of R. damascena products. This research is important as, to the best of our knowledge, it is the first clinical trial to determine the impact of R. damascena products on constipation during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Abbaszadeh et al also reported that the use of Rosa damascene Mill. hydroalcoholic extract in a dose-dependent manner caused diarrhea in dogs [26] . In the present study, in some participants, the frequency increased to 3 to 4 times.…”
Section: Discussionmentioning
confidence: 95%
“…It was then placed in the freezer and prepared in the required dose when used in capsules [22][23][24] ; The dose of Rosa damascene Mill. extract was selected based on the conversion of animal dose to human dose, as in a study in which the dose of 180-190mg/kg caused laxative effects in dogs, and therefore this dose was converted to human dose [25,26] . Lactulose syrup (Sobhan Company; Iran) was used as one of the standard treatments for constipation, along with Rosa damascene Mill.…”
Section: Journal Of Clinical Care and Skillsmentioning
confidence: 99%
“…It is also mainly used in soaps, cosmetics, toiletries and perfumes 7 . Several pharmacological effects such as antibacterial, 8 antimicrobial, 9 anticancer, 10 antidiabetic, 11 anti‐ageing, 12 laxative/purgative, 13 anti‐inflammatory properties as well as its use in aromatherapy for relaxing and the treatment of cardiac diseases were reported for Rosa damascena Mill 14…”
Section: Introductionmentioning
confidence: 99%